The Analysis of the Impact of Population Growth and Economic Development on Urban Land Conversion Case Study of Gresik Regency - Mochammad Roffiqul Pradana Putra (Journal of Economics Development Issues, 2024)
Rapid population growth and significant economic development have an impact on land conversion in urban areas. This study aims to analyze the effect of population growth and economic development on urban land conversion and planning on environmental sustainability and quality of life in urban areas. This research uses a qualitative descriptive approach by collecting secondary data from several sources such as books, government reports, scientific journals, and related publications. The results of the study show that population growth indirectly contributes significantly to land conversion in urban areas. The demand for housing, infrastructure and other public facilities increases as the population increases. Meanwhile, the economic development of a region also has an impact on land conversion. The increase in industrial and commercial sectors has triggered land conversion into industrial areas, shopping centers and businesses. The impact of urban land conversion such as environmental damage, decreased air and water quality, loss of natural habitats, population density. Therefore, the government and related stakeholders must respond by issuing firm policies and sustainable strategies to maintain the main functions of land, preserve green areas and develop efficient infrastructure.